Molecular Dynamics of CH4/N2 Mixtures on a Flexible Graphene Layer: Adsorption and Selectivity Case Study - Vekeman, Jelle; Faginas-Lago, Noelia; Lombardi, Andrea; Sánchez de Merás, Alfredo; García Cuesta, Inmaculada; Rosi, Marzio (Frontiers in Chemistry, 2019)
We theoretically investigate graphene layers, proposing them as membranes of subnanometer size suitable for CH4/N2 separation and gas uptake. The observed potential energy surfaces, representing the intermolecular interactions within the CH4/N2 gaseous mixtures and between these and the graphene layers, have been formulated by adopting the so-called Improved Lennard-Jones (ILJ) potential, which is far more accurate than the traditional Lennard-Jones potential. Previously derived ILJ force fields are used to perform extensive molecular dynamics simulations on graphene's ability to separate and adsorb the CH4/N2 mixture. Furthermore, the intramolecular interactions within graphene were explicitly considered since they are responsible for its flexibility and the consequent out-of-plane movements of the constituting carbon atoms. The effects on the adsorption capacity of graphene caused by introducing its flexibility in the simulations are assessed via comparison of different intramolecular force fields giving account of flexibility against a simplified less realistic model that considers graphene to be rigid. The accuracy of the potentials guarantees a quantitative description of the interactions and trustable results for the dynamics, as long as the appropriate set of intramolecular and intermolecular force fields is chosen. In particular it is shown that only if the flexibility of graphene is explicitly taken into account, a simple united-atom interaction potential can provide correct predictions. Conversely, when using an atomistic model, neglecting in the simulations the intrinsic flexibility of the graphene sheet has a minor effect. From a practical point of view, the global analysis of the whole set of results proves that these nanostructures are versatile materials competitive with other carbon-based adsorbing membranes suitable to cope with CH4 and N2 adsorption.